PENTINGNYA PENGUNGKAPAN STATUS HIV/AIDS ODHA PADA ORANG TERDEKAT - Mutia Galuh; Deny Novani (Jurnal Berkala Kesehatan, 2015)
Abstract The background of revealing the status of HIV can cut through the link of HIV’s infection through self commitment and to be given the comfort in situation and life that is going through. Opening the status of HIV can be beneficial to reduce the act of isolation, increase self acceptance, to be given the safe and healthy sex life, to plan to have a child safely, to plan the future and family and also to be given the ARV medication, the service of management case, with the reference to support group and other advanced service.The aim of this research is to acknowledge some factors which affect ODHA (Orang Dengan HIV/AIDS) in revealing serostatus of HIV to the closest ones. Research method is an explanatory research with cross sectional approach. The sample of this research is the total of population which is 152 people. The data collection was done with questioner and direct observation. Research variable is a respondent characteristic that involves age, gender, education, length of time since being diagnosed HIV, education about HIV/AIDS including the explanation, signs and symptoms, ways of spreading, prevention, treatment, revealing status and the benefit of it, anxiety level, dignity, attitude towards HIV/AIDS disease, ounselor / manager case support, family and couple support, public figure support. Data analysis was done with Chi Square test with trust degree of 95%. The result of variable research that has relation with revealing the status of HIV to the closest ones are education, knowledge, anxiety, dignity, ODHA’s attitude, counselor support, family and couple support. Variable that influences or becomes a predictor is an education, anxiety, and counselor/manager case support. Adjusted score OR or exp (B) education variable in the amount of 4,657 with p = 0,001 (p < 0,05), anxiety variable in the amount of 3,148 with p = 0,020 (p < 0,05, counselor/manager case support in the amount of 3,639 with p = 0,010 ( p < 0,05). Family suggestion and ODHA’s couple are expected to receive ODHA status as it is and also support ODHA to do treatment and care. Family and couple are expected to give company and also full support to ODHA without excluding its existence. Keywords : people living with HIV , disclosure , those closest